NIR/pH-triggered aptamer-functionalized DNA origami nanovehicle for imaging-guided chemo-phototherapy - Mengyue Li; Geng Yang; Yue Zheng; Jiazhen Lv; Wanyi Zhou; Hanxi Zhang; Fengming You; Chunhui Wu; Hong Yang; Yiyao Liu (Journal of Nanobiotechnology, 2023)
Abstract Targeted chemo-phototherapy has received widespread attention in cancer treatment for its advantages in reducing the side effects of chemotherapeutics and improving therapeutic effects. However, safe and efficient targeted-delivery of therapeutic agents remains a major obstacle. Herein, we successfully constructed an AS1411-functionalized triangle DNA origami (TOA) to codeliver chemotherapeutic drug (doxorubicin, DOX) and a photosensitizer (indocyanine green, ICG), denoted as TOADI (DOX/ICG-loaded TOA), for targeted synergistic chemo-phototherapy. In vitro studies show that AS1411 as an aptamer of nucleolin efficiently enhances the nanocarrier’s endocytosis more than 3 times by tumor cells highly expressing nucleolin. Subsequently, TOADI controllably releases the DOX into the nucleus through the photothermal effect of ICG triggered by near-infrared (NIR) laser irradiation, and the acidic environment of lysosomes/endosomes facilitates the release. The downregulated Bcl-2 and upregulated Bax, Cyt c, and cleaved caspase-3 indicate that the synergistic chemo-phototherapeutic effect of TOADI induces the apoptosis of 4T1 cells, causing ~ 80% cell death. In 4T1 tumor-bearing mice, TOADI exhibits 2.5-fold targeted accumulation in tumor region than TODI without AS1411, and 4-fold higher than free ICG, demonstrating its excellent tumor targeting ability in vivo. With the synergetic treatment of DOX and ICG, TOADI shows a significant therapeutic effect of ~ 90% inhibition of tumor growth with negligible systemic toxicity. In addition, TOADI presents outstanding superiority in fluorescence and photothermal imaging. Taken together, this multifunctional DNA origami-based nanosystem with the advantages of specific tumor targeting and controllable drug release provides a new strategy for enhanced cancer therapy.